PEMANFAATAN MEDIA GOOGLE EARTH DALAM PEMBELAJARAN IPS DI SMP NEGERI 1 GARUT - Asna Al Lailiyah, Siti; Mulyana, Eldi; Nopharipaldi Rohman , Slamet (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study was motivated by the importance of using technology-based learning media in Social Studies learning to help students understand materials related to geographical location, maps, and regional conditions. In the learning process, students often experience difficulties in understanding abstract materials when only lecture methods and conventional media are used. Therefore, learning media that can provide real and interactive visualization are needed. One of the media that can be utilized is Google Earth because it is able to display earth imagery, digital maps, and regional conditions in detail. This study aims to describe the utilization of Google Earth media in Social Studies learning at SMP Negeri 1 Garut, determine students’ responses to its use, and identify the advantages and obstacles encountered in its implementation. This research employed a qualitative approach with a descriptive method. Data collection techniques were carried out through interviews, observations, and documentation. The main informant in this study was Mr. Karnata Adiwiria, S.Pd., a Social Studies teacher at SMP Negeri 1 Garut and the head of the Social Studies MGMP in Garut. The results showed that the use of Google Earth made Social Studies learning more interesting, active, and enjoyable. Students appeared more enthusiastic and found it easier to understand directions, locations, coordinate points, and geographical conditions because they could directly observe them through digital displays. The obstacle encountered was that some students still did not fully understand how to use the application, but the teacher overcame this problem by providing direct guidance and peer assistance within groups. Thus, the use of Google Earth was considered effective in supporting Social Studies learning and improving students’ spatial abilities.